Legitimasi Kekuasaan atas Sejarah Keruntuhan Kerajaan Majapahit dalam Wacana Foucault - Muhammad Iqbal Birsyada (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2016)
The history of the collapse of the Majapahit showed the discourse of power. In this context rule has been supporting a particular version of historical knowledge. Applying historical method and multi-dimensional approach, this study aims to find out why the knowledge about the collapse of Majapahit spreading among community members was more tended toward the version that Girindrawardhana as a single actor who overthrow Prabu Brawijaya V. The results of this study indicated that the knowledge among Javanese community about the collapse of Majapahit that stated Girindrawardhana as the sole actor that attacked and subverted the kingdom of Majapahit which at the time was ruled by King Kertabhumi (Brawijaya V) is supported by a wide range of all power of the ruling elite that were largely due to ideological motives. Power and ideology are used as a means of legalizing knowledge.